Chronic Arsenic Exposure in Nanomolar Concentrations Compromises Wound Response and Intercellular Signaling in Airway Epithelial Cells - Sherwood, Cara L. (Oxford University Press, 2013)
Paracrine ATP signaling in the lung epithelium participates in a variety of innate immune functions, including mucociliary clearance, bactericide production, and as an initiating signal in wound repair. We evaluated the effects of chronic low-dose arsenic relevant to U.S. drinking water standards (i.e., 10 ppb [130nM]) on airway epithelial cells. Immortalized human bronchial epithelial cells (16HBE14o-) were exposed to 0, 130, or 330nM arsenic (as Na-arsenite) for 4–5 weeks and examined for wound repair efficiency and ATP-mediated Ca(2+) signaling. We found that chronic arsenic exposure at these low doses slows wound repair and reduces ATP-mediated Ca(2+) signaling. We further show that arsenic compromises ATP-mediated Ca(2+) signaling by altering both Ca(2+) release from intracellular stores (via metabotropic P2Y receptors) and Ca(2+) influx mechanisms (via ionotropic P2X receptors). To better model the effects of arsenic on ATP-mediated Ca(2+) signaling under conditions of natural exposure, we cultured tracheal epithelial cells obtained from mice exposed to control or 50 ppb Na-arsenite supplemented drinking water for 4 weeks. Tracheal epithelial cells from arsenic-exposed mice displayed reduced ATP-mediated Ca(2+) signaling dynamics similar to our in vitro chronic exposure. Our findings demonstrate that chronic arsenic exposure at levels that are commonly found in drinking water (i.e., 10–50 ppb) alters cellular mechanisms critical to airway innate immunity.